Affinity Purification of RNA: Sequence-Specific Capture by Nonionic Morpholino Probes. (December 1997) - Wages, J.M.; Wages, G.M.; Matthews, P.; Weller, D.; Summerton, J.
Nucleic acid isolation for amplification-based diagnostics requires techniques that do not co-purify inhibitors of DNA polymerases. Also, other requirements for an ideal sample preparation technology include ease of use, capability for automation, high recovery and the use of nontoxic reagents. Affinity purification techniques provide high purification factor with minimal sample processing. Hybridization is the affinity interaction specific to nucleic acids and thus provides a uniquely advantageous method for purifying DNA or RNA for subsequent manipulation. Nonionic (morpholino) probes (Neu-Probes™; AntiVirals, Corvallis, OR, USA) have several unique hybridization properties, including resistance to nucleases and the ability to hybridize independently of salt concentration. Therefore, such probes provide advantages over DNA probes for sample preparation by hybridization capture. Three formats for hybridization-based purification of human immunodeficiency virus (HIV) RNA were evaluated using RNA transcripts spiked into crude lysates of normal human plasma. Indirect capture used streptavidin-coated microparticles to capture hybrids of biotinylated capture probes and HIV RNA. Direct capture used particles precoated with probes. In addition, a novel method for acceleration of sequence-specific hybridization was developed and shown to give consistently high recoveries.